1980
DOI: 10.1017/s0033822200010249
|View full text |Cite
|
Sign up to set email alerts
|

Radiocarbon Dating of Calcareous Tufa: How Reliable Data can we Expect?

Abstract: Systematic dating of tufa samples has been undertaken to establish a chronology of tufa deposits in Plitvice National Park, Yugoslavia. We conclude that tufa samples give reproducible data within the time span of ≈ 40,000 years up to recent. The 14C/12C ratio of carbon in the ambient biosphere and hydrosphere gives a detailed picture of the distribution of carbon isotopes in the investigated system. Despite the susceptibility of calcareous material to ambient conditions in the hydrosphere, the original 14C com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0
3

Year Published

1986
1986
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 1 publication
3
29
0
3
Order By: Relevance
“…In a study by Törnqvist et al (1992), however, N. lutea showed a full hardwater effect of about Rf = 500 yr, while the white water lily Nymphaea alba had a terrestrial 14 C age. Differences in 14 C levels for aquatic plants from the same region, as well as high and variable reservoir ages without differences in floating and submerged plants have previously been found (Olsson et al 1969;SrdoË et al 1980). Also, the range of  13 C values is large for the plants analyzed here and spans from -34.2 to -17.5‰ (Table 4).…”
Section: Aquatic Plantsmentioning
confidence: 72%
“…In a study by Törnqvist et al (1992), however, N. lutea showed a full hardwater effect of about Rf = 500 yr, while the white water lily Nymphaea alba had a terrestrial 14 C age. Differences in 14 C levels for aquatic plants from the same region, as well as high and variable reservoir ages without differences in floating and submerged plants have previously been found (Olsson et al 1969;SrdoË et al 1980). Also, the range of  13 C values is large for the plants analyzed here and spans from -34.2 to -17.5‰ (Table 4).…”
Section: Aquatic Plantsmentioning
confidence: 72%
“…Since both tufa and lake sediment are precipitated from the same water and are chemically identical, the measured ao of the tufa sample from year 1919 can be used for the sediment initial activity. We also measured the activity of submerged aquatic plants and found that their activity corresponds to the activity of lake water (Srdoc et al, 1980 …”
Section: Diatom Populationmentioning
confidence: 99%
“…Freshwater reservoir effects can vary significantly within one lake or river [18,25,26], even when only regarding submerged plants [26], or a single fish species from one lake [27]. Furthermore, the FRE influences radiocarbon dating in fjords and estuaries and can lead to site and time specific reservoir ages [28][29][30].…”
Section: Introductionmentioning
confidence: 99%